THE PLACE OF THE GOVERNOR OF OTRAR, GOYIR KHAN, IN THE RELATIONS BETWEEN KHOREZM SHAH ALAUDDIN MUHAMMAD AND GENGHIZ KHAN (Universal International Scientific Journal, 2026)
This article describes the life and work of the patriotic commander Ghoir Khan, his courageous struggle against the Mongol invasion. In addition, information is provided about the political life of the Khorezmshahs of that period.
Keywords: Mongols, Khorezmshahs, Genghis Khan, Goyir Khan, Utrar, Karakorans, Sultan Alauddin Muhammad, Turkan Khotun, Kipchaks.